The Cottoncrest Curse : A Novel - Rubin, Michael H., 1950- (Book collections on Project MUSE., 2014)
The bodies of an elderly colonel and his comely young wife are discovered on the staircase of their stately plantation home, their blood still dripping down the wooden balustrades. Within the sheltered walls of Cottoncrest, Augustine and Rebecca Chastaine have met their deaths under the same shroud of mystery that befell the former owner, who had committed suicide at the end of the Civil War. Locals whisper about the curse of Cottoncrest Plantation, an otherworldly force that has now taken three lives. But Sheriff Raifer Jackson knows that even a specter needs a mortal accomplice, and after investigating the crime scene, he concludes that the apparent murder/suicide is a double homicide, with local peddler Jake Gold as the prime suspect.